The role of PAs in providing mental health care. Issue 12 (21st August 2020) - Mauldin, Sheila G.; Morton-Rias, Dawn; Barnhill, Grady C.; Kozikowski, Andrzej; Hooker, Roderick S.
Abstract : ABSTRACT: The prevalence of psychiatric and substance use disorders in the United States is rising and of growing concern. Because such behavioral conditions are widespread, one approach is to collaborate with various medical professionals to help offset this demand. To address this issue, the frequency and types of mental health conditions encountered by physician assistants (PAs) were assessed. The National Commission on the Certification of Physician Assistants Practice Analysis was examined for the types of mental health conditions encountered across the spectrum of medical and surgical practices. The findings reveal that, in 2015, at least 62% of PAs saw and evaluated mental health conditions and behavioral disorders at least weekly in their settings. These patient diagnoses were seen with variability based on the specialty of the PA. The highest percentage of cases reported by PAs were in psychiatry, followed by general internal medicine, emergency medicine, family medicine, and hospital medicine. With the profession projected to grow, recruiting, retaining, and integrating more PAs into mental health care is a suggested strategy for addressing national provider shortages.